Reproductive phenology of Bruguiera sexangula (Lour.) Poir. in Berbak and Sembilang National Park, South Sumatra - Sarno Sarno; Rujito Agus Suwignyo; Zulkifli Dahlan; Munandar Munandar; Moh Rasyid Ridho (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2018)
Phenology is the study of the period phases which occured naturally in plants. Information about phenology is essential for the sustainable management of mangrove area. During these phases was significantly influenced by the circumstances surrounding environment as ever shines, temperature, and humidity. Observations of the phenology is devoted on mangrove Bruguierasexangula, especially since the phenology information about B. sexangula is still restricted in Berbak and Sembilang National Park, South Sumatra. Research was carried out in February-September 2016. The methods used in this research is a tagging method or labelling on flower buds and observed till the stage of being a mature propagule. Initiation of flowering B. sexangula was occurring in February, the next step was the flowering that occurs from April to June, while the bear season occured from late June-July. The stage of maturation of propagule until October. Harvest time of propagule B. sexangula was conducted in October. Flower initiation of B. sexangula stage to propagule maturity stage takes about 7 months.